Electroanatomic visualization of coronary arteries: a case series to elicit safety, feasibility, and diagnostic value in complex ablation procedures. Issue 4 (4th January 2023) - Fries, Bastian; Johnson, Victoria; Schneider, Nikita; Dörr, Oliver; Chasan, Ritvan; Mathew, Shibu; Hamm, Christian W; Schmitt, Joern
Abstract: Aims: The goal of this case series was to evaluate the feasibility, safety, and advantages of a wire-based approach for the live visualization of coronary arteries (CAs) in an electroanatomic mapping (EAM) system and to assess its diagnostic information. Methods and results: For this single-centre case series, we included procedures in which close proximity of a possible ablation site to any epicardial vessel was suspected. An uncoated-tip guidewire was introduced into the relevant CAs after exclusion of critical CA stenosis by coronary angiography. By connecting this wire to the EAM system using a clip and pin connection, mapping and live visualization of the wire tip is possible, as well as the assessment of the local electrograms within the respective CAs. Procedural wire insertion and intracoronary mapping was performed by EP specialists and was assisted to judge the relevance of CA disease by an interventional cardiologist. A total of nine procedures in nine patients were included in this case series, four ventricular tachycardia ablation procedures and five procedures for the ablation of premature ventricular contractions. The left CAs were mapped in eight cases and the right CA was mapped in one case. In two cases, epicardial mapping was combined with visualization of the right or left CAs. There were no complications attributed to coronary wiring and mapping in this case. Conclusion: We demonstrated the feasibility and safety of CA visualization and integration in an EAM. The live visualization of the CAs added valuable information without the need for preprocedural planning or the purchase of separate software. Electroanatomic visualization was achieved intraprocedurally in a safe and straightforward manner, adding critical diagnostic information without excessive costs or risks. Graphical Abstract: Graphical Abstract